Analysis of betaine levels in cereals, pseudocereals and their products - Jovana Kojić; Jelena Krulj; Nebojša Ilić; Eva Lončar; Lato Pezo; Anamarija Mandić; Marija Bodroža Solarov (Journal of Functional Foods, 2017)
Betaine has a range of health benefits and therefore has been recommended as a functional ingredient in dietary supplements. The main dietary sources of betaine are processed grains such as bread, biscuits, cereals, pasta and similar products. This study describes analysis of 54 samples of cereals and pseudocereals for betaine content by using HPLC – ELSD method. By using this approach betaine levels were identified, quantified and compared. Analysis of variance showed significant differences between analyzed samples (from <LOQ mostly in gluten free products to 328.5 mg/100 g DM in enriched plain biscuit with molasses). PCA analysis gave two large clusters, one for gluten-free samples and the second cluster containing all of the remaining samples. As a final result the average betaine levels in analyzed food samples were in the following order: buckwheat < millet < wheat < oats < rye < barley < amaranth < spelt.